Internal Control Model Of Datok Sulaiman Palopo Modern Islamic Boarding School - Nurfadilah, Nurfadilah (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2022)
This study aims to analyze the internal control model of the Modern Islamic Boarding School Datok Sulaiman (PMDS) Palopo and the suitability of the internal control model applied to the COSO (Committee of Sponsoring Organization of the Treadway Commission) concept which consists of five components, namely: 1) Control Environment; 2) Risk Assessment; 3) Control Procedures; 4) Monitoring; 5) Information and Communication. This research uses qualitative research with a case study approach. The data obtained were then analyzed using the Miles-Huberman model, starting from data collection, data reduction, data presentation to conclusions. The results of this study found that the implementation of the internal control system in PMDS was quite good and was in accordance with the COSO concept. It's just that there are still weaknesses in some parts, such as the separation of responsibilities in the finance department and the application of Islamic boarding school accounting. However, PMDS in creating reliable internal control always instills Religious values, namely: Amanah and Barokah